2016
DOI: 10.1136/sextrans-2015-052213
|View full text |Cite
|
Sign up to set email alerts
|

False-negative type-specific glycoprotein G antibody responses in STI clinic patients with recurrent HSV-1 or HSV-2 DNA positive genital herpes, The Netherlands

Abstract: Commercial type-specific gG HSV-1 or HSV-2 antibody assays were false negative in 12-30% of patients with recurrent HSV-1 or HSV-2 DNA positive genital lesions. The clinical and epidemiological use of type-specific HSV serology can be hampered by false-negative results, especially if based on a single test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A further important misclassification bias is related to the inaccuracies of the STI testing algorithms used. In particular, HSV-2 serological testing including the testing algorithm used in the UHSBS is characterized by relatively poor sensitivity and specificity [ 34 , 35 ]. A metanalysis of the performance of HSV-2 serological testing in sub Saharan Africa found that the Kalon HSV-2 EIA used in the UHSBS had a sensitivity of 95% (95% CI: 93%–97%) and a specificity of 91% (95% CI: 86%–95%) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further important misclassification bias is related to the inaccuracies of the STI testing algorithms used. In particular, HSV-2 serological testing including the testing algorithm used in the UHSBS is characterized by relatively poor sensitivity and specificity [ 34 , 35 ]. A metanalysis of the performance of HSV-2 serological testing in sub Saharan Africa found that the Kalon HSV-2 EIA used in the UHSBS had a sensitivity of 95% (95% CI: 93%–97%) and a specificity of 91% (95% CI: 86%–95%) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Bradley et al, in 2005–2010, the seroprevalence of HSV‐1 was 53.9%, and the seroprevalence of HSV‐2 was 15.7% . These numbers might be even higher because the epidemiological use of type‐specific HSV serology can be hampered by false‐negative results, especially if based on a single test, and the antibodies formed against either virus are highly cross‐reactive .…”
Section: Discussionmentioning
confidence: 99%
“…It is not uncommon to have a false‐negative result because low‐level HSV antibodies can be below the level of detection of the HSV serologic assays; therefore, the recipient's pretransplant serology could have been a false‐negative result. False‐negative test results can be as high as 30%, depending on the assay in use .…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that 12–30% of patients lose their HSV type-specific IgG antibodies depending on their HSV types and the test used. 37…”
Section: Diagnosismentioning
confidence: 99%